PENGARUH LOKASI, KUALITAS PRODUK DAN EVENT TERHADAP KEPUTUSAN BERWISATA KE MUSEUM BANK INDONESIA JAKARTA - Syiar Fatiara; Parlagutan Silitonga; Nova Eviana (LPPM and Travel Operation Department Universitas Asa Indonesia, 2017)
This research aims to analyze the effect of location (X1), quality of product (X2), and event (X3) toward the decision of travelling (Y) partially and simultaneously. Using Slovin formula, samples used in this research are 100 of the visitors of Bank Indonesia Museum Jakarta, with accidental sampling technique. Data analysis uses multiple linear regression with the assistance of SPSS ver. 20 software. The research shows that location, quality of product, and event have significant influences partially and simultaneously, and contribute 52.41% toward the decision of traveling (Y) as well.